1996
DOI: 10.1161/01.cir.94.12.3271
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive Evaluation of Intrarenal Oxygenation With BOLD MRI

Abstract: BOLD MRI can be used to monitor changes in intrarenal oxygenation in humans in a noninvasive fashion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

29
335
2
1

Year Published

1996
1996
2020
2020

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 375 publications
(367 citation statements)
references
References 21 publications
29
335
2
1
Order By: Relevance
“…Prasad et al demonstrated in conscious volunteers that 20 mg of furosemide increased medullary oxygenation, using the blood oxygen level-dependent magnetic resonance imaging technique (BOLD MRI) [16]. In contrast, acetaz olamide, which inhibits tubular reabsorption of the proximal tubules in the cortex and which does not aff ect medullary PO 2 in experimental studies, did not aff ect medullary oxygenation.…”
Section: Eff Ects Of Diureti Cs On Renal Oxygenation In the Postoperamentioning
confidence: 99%
“…Prasad et al demonstrated in conscious volunteers that 20 mg of furosemide increased medullary oxygenation, using the blood oxygen level-dependent magnetic resonance imaging technique (BOLD MRI) [16]. In contrast, acetaz olamide, which inhibits tubular reabsorption of the proximal tubules in the cortex and which does not aff ect medullary PO 2 in experimental studies, did not aff ect medullary oxygenation.…”
Section: Eff Ects Of Diureti Cs On Renal Oxygenation In the Postoperamentioning
confidence: 99%
“…Blood oxygen level dependant (BOLD) MRI has the ability to detect changes in hemoglobin oxygenation due to the dephasing effects of deoxyhemoglobin (26,27). This allows for a noninvasive measure of renal tissue oxygenation (28), and has been advocated for use in differentiating ATN and rejection in the transplant kidney (29).…”
Section: Other Functional Mri Techniquesmentioning
confidence: 99%
“…6) may be an indicator of acute rejection. Further support for this consideration comes from the finding that functional T2-mapping (BOLD) MRI has been shown to differentiate ATN and acute rejection (27,57).…”
Section: Acute Rejectionmentioning
confidence: 99%
“…Differences in concentrations of deoxyhemoglobin modulate microscopic field gradients in the vicinity of blood cells and vessels. 79 These intravoxel alterations in the magnetic field cause loss of phase coherence, which leads to signal loss on gradient echo T2-weighted images, the so-called BOLD contrast.…”
Section: Bold Imagingmentioning
confidence: 99%